The Effect Of Peer-Nurses\\\' Lecturing On Critical Units Nurses' Retaining Knowledge Of Electrocardiogram Interpretation - Abbasali Ebrahimian; Ali Fakhr-Movahedi; Hossein Davari; Maedeh Tourdeh (Tehran University of Medical Sciences, 2015)
Background and Aim: Learning basic issues in nursing requires new strategies that can enhance knowledge retention among nurses. This study aimed to determine the effect of lecturing by peer-nurses on critical units nurses' retaining knowledge of electrocardiogram (ECG) interpretation. Materials and Methods: In this experimental study, two units (as test and control groups) were selected randomly from among critical care units of Semnan University of Medical Sciences hospitals. First, a pretest was performed on nurses in both groups. Then, the nurses of test group were trained by a peer-nurse how to interpret ECGs. A posttest was performed on the two groups both a week and a year later. Finally, the data were analyzed using Pearson's correlation coefficient, t-paired and t-tests. Results: The mean of nurses' scores of ECG interpretation in pretest was 9.55±2.73 in the test group and 10.82±3.43 in the control group. In the first posttest, mean scores of nurses' knowledge in test and control groups were 15.27±2.57 and 11.36±3.29, respectively. In the second posttest, nurses' mean scores in test and control groups were 10.82±4.07 and 11.33±2.95, respectively. There was a significant difference (p0.05). Conclusion: Lecturing by peer-nurses can enhance nurses' knowledge about ECG interpretation in the short run, but it cannot enhance knowledge retention. So it is suggested that other educational methods be used in nurses' in-service training programs designed for ECG interpretation.